Controlling the solvothermal synthesis of the mixed vanadium – molybdenum oxides by employing surfractants - Sviridova, Tatyana V. (Journal of the Belarusian State University. Chemistry, 2020)
It is shown that the solvothermal synthesis of mixed vanadium – molybdenum oxide 0.5V2O5 : 0.5MoO3 in the presence of surfactants permits one to exert an effective control over the phase formation and to obtain needle-like crystals exhibiting high aspect ratio. The synthesis in the presence of polyethylene-glycol (non-ionogenic surfactant) ensures blocking of the terminal OH-groups at the surface of mixed oxide thus preventing the agglomeration of arising grid structures with high surface-to-volume ratio showing much promise as the heterogeneous catalysts.
Keywords: mixed vanadium – molybdenum oxide; solvothermal synthesis; surfactants; grid structures